(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
this article discusses issues related to approaches to assessing creditworthiness in the process of lending to small and medium-sized businesses. Analyzed Well-known methods for assessing creditworthiness are analyzed and revealed and their advantages and disadvantages are identified. Suggestions are given for developing the lending process and improving methods for assessing the creditworthiness of borrowers-small and medium-sized businesses.